2016
DOI: 10.1089/gtmb.2015.0333
|View full text |Cite
|
Sign up to set email alerts
|

XPG Gene Polymorphisms and the Risk of Gastric Cardia Adenocarcinoma

Abstract: Our findings indicate that the rs751402 C/T SNP has potential as a predictive marker for the risk of GCA and that carriers of the T/T genotype should receive periodic upper gastrointestinal fiber tests to facilitate the early detection and early treatment of GCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The final meta-analysis included 47 articles. There were 22 articles with 12,833 cases and 151,86 controls for rs1047768 T>C [79, 12, 1431], 14 studies with 11,327 cases and 12,684 controls for rs2296147 T>C [911, 13, 18, 24, 2628, 32–37], 11 studies with 5,898 cases and 7,448 controls for rs2227869 G>C [8, 9, 14, 17, 18, 20, 22, 25, 3840], 17 studies with 9,826 cases and 10,552 controls for rs2094258 C>T [10, 11, 18, 24, 2628, 34–37, 41–46], 21 studies with 10,369 cases and 11,207 controls for rs751402 C>T [10, 13, 24, 2629, 31, 32, 36, 37, 4245, 4752], and 14 studies with 10,873 cases and 12,535 controls for rs873601 G>A [911, 18, 24, 2628, 32, 34, 36, 5254]. A flow chart summarizing the process of relevant study identification is shown in Figure 1, and the study characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The final meta-analysis included 47 articles. There were 22 articles with 12,833 cases and 151,86 controls for rs1047768 T>C [79, 12, 1431], 14 studies with 11,327 cases and 12,684 controls for rs2296147 T>C [911, 13, 18, 24, 2628, 32–37], 11 studies with 5,898 cases and 7,448 controls for rs2227869 G>C [8, 9, 14, 17, 18, 20, 22, 25, 3840], 17 studies with 9,826 cases and 10,552 controls for rs2094258 C>T [10, 11, 18, 24, 2628, 34–37, 41–46], 21 studies with 10,369 cases and 11,207 controls for rs751402 C>T [10, 13, 24, 2629, 31, 32, 36, 37, 4245, 4752], and 14 studies with 10,873 cases and 12,535 controls for rs873601 G>A [911, 18, 24, 2628, 32, 34, 36, 5254]. A flow chart summarizing the process of relevant study identification is shown in Figure 1, and the study characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The association with gastric cancer risk was based on 6 case–control studies, and our results were in accordance with Duan et al [ 27 ] However, the results were inconsistent with other studies, which failed to find significant association between rs751402 polymorphisms and gastric cancer. [ 28 30 ] Zhou et al found that TT genotype was associated with an increasing risk of gastric cardia adenocarcinoma. [ 30 ] The controversial results might be partially due to the variations in the sample sizes and the control group sampling methods.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 30 ] Zhou et al found that TT genotype was associated with an increasing risk of gastric cardia adenocarcinoma. [ 30 ] The controversial results might be partially due to the variations in the sample sizes and the control group sampling methods. In Duan et al’ studies, the sample size was relatively small, and the healthy controls were patients with mild superficial gastritis receiving endoscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…In these publications, sample sizes ranged from 96 to 1900 cases and from 101 to 1977 control subjects. Among the studies, 10 focused on gastric cancer [ 21 , 23 , 27 , 29 , 30 , 32 34 , 38 , 39 ], three focused on breast cancer [ 25 , 35 , 36 ], two focused on hepatocellular carcinoma [ 20 , 37 ], and one each focused on lung cancer [ 19 ], oral squamous cell carcinoma [ 22 ], salivary gland tumor [ 24 ], nasopharyngeal carcinoma [ 26 ], neuroblastoma [ 28 ], colorectal cancer [ 31 ], and prostate cancer [ 40 ]. Of the publications, 12 had quality scores higher than nine, and 10 had quality scores of no more than nine.…”
Section: Resultsmentioning
confidence: 99%